Special papersMyocardial infarction caused by pharmacological substances – case description and literature review - Kameczura, Tomasz; Bryniarski, Leszek; Surowiec, Sławomir; Kocowska, Maryla; Kawecka-Jaszcz, Kalina; Czarnecka, Danuta (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2013)
Myocardial infarction (MI) is most commonly caused by atherosclerosis and/or inflammatory processes of coronary artery walls. The consequence of those phenomena is instability of the atherosclerotic plaque, activation of the coagulation cascade and thrombus formation which occludes the lumen of the vessel. Vasospasm and microembolisation may participate in MI pathogenesis. In young individuals with diagnosis of MI, coronarography often reveals no pathologies. Is reported that MIs without significant changes of the coronary arteries occur in 1% to 12% of patients. In this article we focus on chemical substances, medicines among them, which can be a cause of MI.